Simultaneous Determination of Paracetamol, Acetyl Salicylic Acid, Mefenamic Acid and Cetirizine Dihydrochloride in the Pharmaceutical Dosage Form - Freddy H. Havaldar; Dharmendra L. Vairal (E-Journal of Chemistry)
A simple, specific, accurate and economical isocratic reversed phase liquid chromatographic (RP-HPLC) method was developed and subsequently validated for the determination of paracetamol, acetyl salicylic acid, mefenamic acid and cetirizine dihydrochloride. Separation was achieved with a Nucleodur 100 C–18 column having 250 × 4.6 mm i.d. with 5 µm particle size and disodium hydrogen phosphate buffer adjusted to pH 6.5 using diluted orthophosphoric acid and acetonitrile (60:40 v∕v) as eluent at a constant flow rate of 1.0 mL per min. UV detection was performed at 220 nm. The retention time of acetyl salicylic acid, paracetamol, mefenamic acid and cetirizine dihydrochloride were 2.01 min, 2.92 min, 4.91 min and 10.2 min respectively. This method is simple, rapid and selective and can be used for routine analysis of analgesic and antipyretic drugs in pharmaceutical formulations. The proposed method was validated and successfully used for estimation of paracetamol, acetyl salicylic acid, mefenamic acid and cetirizine dihydrochloride in the pharmaceutical dosage form.